Land rental and sales markets in Paraguay - Thomas Masterson (Levy Economics Institute of Bard College, 2007)
This paper examines the claim that the land rental market can be an effective means of redistributing access to, if not ownership of, land to the rural poor, using Paraguay as our model. The land sales market is also examined. The land rental market in Paraguay's rural areas is found to be very thin, due at least in part to a lack of available credit for inputs. Renting-in substantial amounts of land is found to contribute significantly to household per-capita income.
Keywords: D39; O12; Q15; 330; Distribution; Land Markets; Land Ownership; Paraguay